Harmonisasi Kewenangan Pembuatan Risalah Lelang Antara Notaris Dengan Pejabat Lelang - Dewi, Ni Made Ayu Sintya; Resen, Made Gde Subha Karma (Acta Comitas : Jurnal Hukum Kenotariatan, 2021)
This journal’s purpose is to understand the harmonization of authority arrangements for making auction minutes and to find out the evidentiary strength of auction minutes. This research uses normative legal research with an approach to the concept of law and legislation. Based on the lex special derogate legi generale principle, the authority to prepare auction minutes is based on Staatsblad No. 189 which was promulgated in 1908 concerning Vendu Reglement / VR (hereinafter referred to as Tender Regulations) which regulate the authority to make Minutes of Auction rests with the Auction Officer not the Notary Public. Although a Notary Public can be appointed as Class II Auction Officer according to Article 7 the Vendue Intructie in Indonesian is called an auction instruction Jo. Regulation of the Minister of Finance of the Republic of Indonesia Number 175 / PMK.06 / 2010 concerning Class II Auction Officers (hereinafter referred to as PMK Class II Auction Officers), however this authority is given the capacity of a Notary as Class II Auction Officer and not the capacity as a Notary. The power of proof of the auction minutes according to Article 1868 of the Criminal Code, the minutes of auction fulfilling the three elements of the deed must be made by a General Official, the deed is determined by law and the General Official who makes it must be authorized to make the deed so that it is said that the Minutes of Auction are authentic deeds having the power of proof that perfect.   Tujuan jurnal ini yaitu untuk memahmi harmonisasi pengaturan kewenangan Pembuatan Risalah Lelang dan untuk mengetahui kekuatan pembuktian risalah lelang. Penelitian ini menggunakan penelitian hukum normatif dengan pendekatan konsep hukum dan perundang-undangan. Berdasarkan asas lex special derogate legi generale pengaturan kewenangan Pembuatan Risalah Lelang adalah berdasarkan Staatsblad No. 189 yang diundangkan pada tahun 1908 tentang Vendu Reglement/VR (selanjutnya disebut Peraturan Lelang) yang mengatur kewenangan membuat Risalah Lelang terdapat pada Pejabat Lelang bukan pada Notaris. Walaupun Notaris dapat diangkat sebagai Pejabat Lelang Kelas II menurut Pasal 7 Vendue Intructie dalam bahasa Indonesia disebut Intruksi lelang Jo. Peraturan Menteri Keuangan Republik Indonesia Nomor 175/PMK.06/2010 tentang Pejabat Lelang Kelas II (selanjutnya disebut PMK Pejabat Lelang Kelas II), namun wewenang itu diberikan kapasitas Notaris sebagai Pejabat Lelang Kelas II dan bukan kapasitasnya sebagai Notaris. Kekuatan pembuktian risalah lelang menurut Pasal 1868 KUHPer, Risalah lelang memenuhi ketiga unsur akta itu harus dibuat seorang  Pejabat Umum, akta  itu  ditentukan oleh undang-undang dan Pejabat  Umum  yang membuat harus  berwenang membuat akta tersebut sehingga dikatakan Risalah Lelang merupakan akta otentik memiliki kekuatan pembuktian yang sempurna.